Effects of cropping system and varieties on the rice growth and yield in acid sulphate soils of tidal swampland - Izhar Khairullah (Universitas Gadjah Mada, 2021)
Swampland plays a critical function in agriculture, specifically in growing rice production. The study aimed to determine the effects of cropping systems and varieties on the rice growth and yield in acid sulfate soil of tidal swampland. The experiment was conducted in a potential acid sulphate soils in Kapuas Regency, Central Kalimantan Province. The experiment was arranged in a split plot design with three replications. The main plot consisted of three HYV’s of rice, namely Inpara 8, Inpari 32, and Margasari. The subplot consisted of five cropping systems, namely, Jarwo 2:1A, Jarwo 2:1B, Jarwo 2:1C, Hazton, and Tegel.  The plot size was 4 m x 5 m. The variables observed included initial soil properties, plant growth, and yield components. The jajar legowo cropping system in this study was not able to increase rice yields in acid sulphate soil.  There was an interaction effect of cropping systems and varieties on the plant height and number of tillers at vegetative phase. At generative and pre-harvest phases, there was significant single effect of variety and cropping system in the planting height and number of tillers, respectively. Both cropping system and variety significantly affected the number of panicles per hill, while panicle length, grain per panicle and grain yield were only affected by variety.  There was no significant effect of both factors on the number of filled grains per panicle.  Inpara 8 variety achieved the highest grain yield, which was 6.78 ton.ha-1 or equivalent to 4.34 ton.ha-1 of 14 % water content.